PENGGUNAAN SAKO DALAM SUKU MANDAILIANG OLEH KETURUNAN YANG TIDAK BERHAK DI KAMPUANG GADANG CUBADAK RANDAH NAGARI TANJUANG BONAI KABUPATEN TANAH DATAR - Yuli Maharani; Zulfikar Jayakusuma; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Customary law is an unwritten law recognized in the Constitution. One of the Minangkabauindigenous people groups who still adhere to their customs and practice their customary law isthe Tanjung Bonai indigenous Kenagarian community. In the Tanjung Bonai indigenouscommunity, it is known as the inheritance of the title of prince or an intangible inheritance,which in the Tanjung Bonai Kenagarian indigenous community is known as sako which is stillthickly passed down from generation to generation. However, in reality the problem regardingthe inheritance of the sako title has created a conflict between the descendants of Dt.Domo andMuslims. Where Muslims are actually immigrants who claim to be mamak to the Dt.Domo andclaim that the Dt.Domo have become extinct.The type of research used in this study is sociological juridical, so in this study the authorscollected data through interviews. This research was conducted in Nagari Tanjung Bonai, TanahDatar District. While the entire population and sample of parties related to the problems studiedin this study, the data sources used are primary data, secondary data and tertiary data.From the research problem there are two main things that can be concluded, first, thefactors causing the use of sako in the Mandailing tribe by illegitimate descendants in KampungGadang Cubadak Randah Nagari Tanjung Bonai Tanah Datar Regency are roads in AliahUrang Paladang, Cupak in Aliah Urang Panggaleh, Karambiah indak tumbua di mato, Alahlime deck binalu. Second, the customary settlement for the use of sako in the Mandailing tribe byillegitimate descendants in Gadang Cubadak Randah Nagari Tanjung Bonai Village, TanahDatar Regency is based on the concept of